Qualidade da madeira de três espécies de Eucalyptus resultante da combinação dos métodos de secagem ao ar livre e convencional - Rosso, Silviana (2006)
This work aims at evaluating the wood quality of Eucalyptus citriodora, Eucalyptus grandis and Eucalyptus saligna, resulting from the combination of open air and conventional drying methods during the winter and the summer, and also the efficiency of that combination in relation to both the drying rate and the time. In each season, 40 planks of every Eucalyptus specie were evaluated in three different stages of the whole process: before the beginning of the open air drying, after its end when the wood reached about 25% of moisture, and at the end of the conventional drying with 12% of moisture. The main defects in those phases were rifts, colapse, and superficial hardening. The results show that in the summer the drying time in the open air was shorter than in the winter. The drying rate was higher in that season for the three species. The highest rates of rifts of top were found in Eucalyptus citriodora in the summer and in the Eucalyptus grandis in the winter. After the combined drying in the summer, the species that had more planks with rifts of superficie were Eucalyptus citriodora and Eucalyptus saligna, with numbers of 78,1% and 46,9%, respectively. The Eucalyptus saligna planks presented in the two seasons 37% of arch format which was worst at the end of the process of combined drying. The Eucalyptus grandis was the only specie that had bending of 3,13% in the winter. In the final evaluation, 100% of Eucalyptus citriodora and Eucalyptus saligna presented drying tensions in the two seasons. However, Eucalyptus grandis was 75% affected by that problem in the summer and 100% in the winter. None of the three species took both canoe format and colapse in any of the planks.